Adipose Inflammation and Macrophage Infiltration After Binge Ethanol and Burn Injury. (1st August 2013) - Qin, Yuanyuan; Hamilton, Jillian L.; Bird, Melanie D.; Chen, Michael M.; Ramirez, Luis; Zahs, Anita; Kovacs, Elizabeth J.; Makowski, Liza
<x xml:space="preserve">Abstract</x> Background Ethanol (EtOH) exposure prior to traumatic injury, such as a burn, elevates systemic and local inflammatory responses and increases morbidity and mortality. Adipose is a large tissue mass that is often inflamed during obesity or other stresses, which disturbs metabolic homeostasis. To date, there has been little investigation into the inflammatory response of adipose tissue after combined EtOH exposure and burn injury. Methods Two EtOH exposure regimens were utilized to examine the role of inflammation in adipose tissue after EtOH and burn injury. Mice were either given a single or episodic binge exposure to EtOH or saline followed by scald (burn) or sham injury 30 minutes later. Twenty‐four hours post injury, serum and adipose tissue were collected for assessment of inflammatory mediators. Results Single binge EtOH alone induced no inflammation in adipose when compared with sham vehicle‐treated mice. However, single binge EtOH followed by burn injury induced significant elevations in mRNA and protein concentrations of pro‐inflammatory mediators interleukin‐6 (IL‐6), KC, and monocyte chemoattractant protein 1 compared with either insult alone or sham vehicle group. Additionally, EtOH exposure and burn injury significantly blunted inducible nitric oxide synthase (iNOS), indicating a complex inflammatory response. Episodic binge EtOH exposure followed by burn injury exacerbated the postburn adipose inflammatory response. The magnitude of the episodic binge‐induced inflammatory parameters postburn were 2‐ to 5‐fold greater than the response detected after a single exposure of EtOH, indicating EtOH‐induced potentiation of burn‐induced inflammatory response. Finally, inflammatory loci and crown‐like structures in adipose were significantly increased by episodic binge EtOH and burn injury. Conclusions This is the first report of binge and burn‐induced crown‐like structure formation. Evidence presented herein suggests an important role for alcohol and burn as an additional mediator of adipose inflammation in postburn injury, a common complication in burn patients.